Outh and Value Change: A Sociological Approach Amid Contemporary Social Transformations - Lamria Samia (Journal of Informatics Education and Research, 2025)
Contemporary societies have experienced profound social and cultural transformations in recent decades, which have clearly reflected on the value systems, especially among youth who represent the primary drivers of social change. This study aims to analyze the phenomenon of value change among youth within the context of global and local transformations, focusing on the Algerian case as a model, relying on a sociological approach combining theoretical analysis and field study. The descriptive-analytical method was employed, supported by field data collected through surveys and in-depth interviews with youth aged between 18 and 30 years. The results indicate a decline in some traditional values related to family solidarity and collective belonging, alongside a rise in values of individualism, material ambition, and digital cultural openness. The study also reveals a clear influence of social media, cultural globalization, and economic transformations on patterns of thinking and value-related behavior. The paper concludes that value change among youth represents both a challenge and an opportunity, requiring the formulation of renewed educational and cultural policies that balance authentic values with contemporary demands